Improvement of Science Learning Outcomes Electrical Circuits Materials through Problem Based Learnig Models Students of Class VI Semester I SD Negeri Karangtalun 02 Cilacap - Anita Wijayanti; Subuh Anggoro; Naning Aisah; Dwi Retnaningsih (UM Purwokerto Press, 2023)
The goal of this study is to ascertain if the problem-based learning approach has improved the learning results for class VI students at SD Negeri Karangtalun 02 Cilacap. 34 students in grade 6 SD Negeri Karangtalun 02, including 16 male and 18 female students, participated in this sort of classroom action research study. The poor scientific learning outcomes in the subject of electrical circuits are what spurred this investigation. Observation, testing, and documenting were the approaches employed for data collecting. There were two cycles to this study. The findings demonstrated that using problem-based learning to teach students about basic electrical circuits might enhance their learning outcomes. Pre-cycle students' average learning achievements were just 66.07 After using the PBL model, the average value rose to 74.57 in cycle I and to 84.29 in cycle II. According to these findings, the Problem Based Learning (PBL) teaching approach may increase scientific learning outcomes in class VI students' first semester at SD Negeri Karangtalun 02 by 91%.